Upregulation of Matrix Metalloproteinase-9 in Primary Cultured Rat Astrocytes Induced by 2-Chloroethanol Via MAPK Signal Pathways - Wang, Tong; Liao, Yingjun; Sun, Qi; Tang, Hongge; Wang, Gaoyang; Zhao, Fenghong; Jin, Yaping (Frontiers in Cellular Neuroscience, 2017)
2-Chloroethanol (2-CE) is one of the reactive metabolites of 1,2-DCE in vivo, which might contribute to brain edema formation induced by 1,2-dichloroethane (1,2-DCE) poisoning. Thus, the aim of this study was to explore the roles of mitogen-activated protein kinase (MAPK) signal pathways in upregulation of matrix metalloproteinase-9 (MMP-9) in 2-CE exposed rat astrocytes. Expression of p38 MAPK (p38), extracellular signal regulated protein kinase (ERK), c-Jun N-terminal kinase (JNK) and MMP-9 at both protein and gene levels in astrocytes were examined by western blot and real-time RT-PCR analysis. Findings from this study disclosed that both protein and mRNA levels of MMP-9 in 2-CE exposed astrocytes increased significantly. Meanwhile, protein levels of phosphorylated p38 (p-p38), ERK1/2 (p-ERK1/2) and JNK1/2 (p-JNK1/2) in 2-CE exposed astrocytes also increased significantly. Moreover, in response to reduced protein levels of p-p38, p-ERK1/2 and p-JNK1/2 achieved by supplement with their specific inhibitors, both protein and mRNA levels of MMP-9 decreased significantly, suggested that activation of MAPK signal pathways might play the key roles in upregulation of MMP-9 expression at the transcriptional level in 2-CE exposed astrocytes. Furthermore, since pretreatment of n-acetyl-l-cysteine (NAC), the scavenger of reactive oxygen species (ROS), could attenuate the elevated levels of MMP-9, p-p38, p-ERK2 and p-JNK1/2 in 2-CE exposed astrocytes, activation of MAPK signal pathways in 2-CE exposed astrocytes could be mediated partially by ROS, which was most likely generated in the metabolism of 2-CE.